Activin A-mediated epithelial de-differentiation contributes to injury repair in an in vitro gastrointestinal reflux model. (November 2019) - Roudebush, Cedric; Catala-Valentin, Alma; Andl, Thomas; Le Bras, Gregoire F.; Andl, Claudia D.
Graphical abstract: Highlights: Bile acid injury caused by gastroesophageal reflux induces Activin A. Activin A-dependent repair involves cell motility and stem cell marker upregulation. Chronic bile acid exposure induces epithelial cell de-differentiation. Traits of Barrett's esophagus may arise from cyclic repair following paligenosis. Abstract: Reflux esophagitis is a result of esophageal exposure to acid and bile during episodes of gastroesophageal reflux. Aside from chemical injury to the esophageal epithelium, it has been shown that acid and bile induce cytokine-mediated injury by stimulating the release of pro-inflammatory cytokines. During the repair and healing process following reflux injury, the squamous esophageal cells are replaced with a columnar epithelium causing Barrett's metaplasia, which predisposes patients to esophageal adenocarcinoma. We identified a novel player in gastroesophageal reflux injury, the TGFβ family member Activin A (ActA), which is a known regulator of inflammation and tissue repair. In this study, we show that in response to bile salt and acidified media (pH 4) exposure, emulating the milieu to which the distal esophagus is exposed during gastroesophageal reflux, long-term treated, tolerant esophageal keratinocytes exhibit increased ActA secretion and a pro-inflammatory cytokine signature. Furthermore, we noted increased motility and expression of the stem cell markers SOX9, LGR5 and DCLK1 supporting the notion that repair mechanisms were activated in the bile salt/acid-tolerant keratinocytes. Additionally, these experiments demonstrated that de-differentiation as characterized by the induction of YAP1, FOXO3 and KRT17 was altered by ActA/TGFβ signaling. Collectively, our results suggest a pivotal role for ActA in the inflammatory GERD environment by modulating esophageal tissue repair and de-differentiation.